2020
DOI: 10.21203/rs.3.rs-26344/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Broad-spectrum inhibition of coronavirus main and papain-like proteases by HCV drugs

Abstract: Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 has led to over 200,000 deaths thus far. We screened a library of approved antiviral drugs against the two SARS-CoV-2 proteases, 3C-like/main protease (3CLpro/Mpro) and papain-like protease (PLpro), which are essential for viral replication and attractive drug targets. Three HCV protease inhibitors were tested and found to inhibit 3CLpro and PLpro enzymes from Alpha-, Beta- and Gamma-coronaviruses. Anti-HIV drugs had no activity. Boceprevir and telaprevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
1
32
1
Order By: Relevance
“…However, the addition of 1 to 100 µM famotidine to the reaction does not signi cantly reduce the amount of ISG15 cleaved during the assay ( Figure 1, lanes 4 to 6), thus suggesting that famotidine does not inhibit SARS-CoV-2 PLpro. A previous virtual screening report 26 suggested that famotidine might bind to the 3 chymotrypsinlike protease (3CLpro), more commonly referred to as the main protease (Mpro), however this mechanism was recently discounted 27 .…”
Section: Antiviral Activity Famotidine Does Not Bind To Sars-cov-2 Prmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the addition of 1 to 100 µM famotidine to the reaction does not signi cantly reduce the amount of ISG15 cleaved during the assay ( Figure 1, lanes 4 to 6), thus suggesting that famotidine does not inhibit SARS-CoV-2 PLpro. A previous virtual screening report 26 suggested that famotidine might bind to the 3 chymotrypsinlike protease (3CLpro), more commonly referred to as the main protease (Mpro), however this mechanism was recently discounted 27 .…”
Section: Antiviral Activity Famotidine Does Not Bind To Sars-cov-2 Prmentioning
confidence: 99%
“…proteases (PLpro or Mpro) 27 . Vero E6-based cell assays also indicate that famotidine has no direct antiviral activity in this cell line, although antiviral activity in cells that express H 2 has not been tested.…”
Section: Famotidine Reaches Functionally Relevant Systemic Concentratmentioning
confidence: 99%
“…In the course of our study, three other groups reported that boceprevir can inhibit SARSCoV2 M pro at low micromolar concentrations in vitro (48)(49)(50). Two of these studies included crystal structures of SARSCoV2 M pro complexed with boceprevir (PDB 6WNP and 7C6S) that validate our manually docked model (49,50).…”
Section: Discussionmentioning
confidence: 67%
“…In the course of our study, three other groups reported that boceprevir can inhibit SARSCoV2 M pro at low micromolar concentrations in vitro (48)(49)(50). Two of these studies included crystal structures of SARSCoV2 M pro complexed with boceprevir (PDB 6WNP and 7C6S) that validate our manually docked model (49,50). Alignment of these structures to that of 13b complexed with SARSCoV2 M pro indicates that the proline ring of boceprevir can indeed mimic a turn taken by the backbone of linear protease inhibitors at the P2 position ( Supporting Fig 4), confirming our original hypothesis (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation